2016
DOI: 10.1002/mbo3.341
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans p38 MAPK Gene plays a key role in protection from mycobacteria

Abstract: Mitogen‐activated protein kinases (MAPK) are critical mediators of cellular responses to pathogens and are activated in response to infection, but investigation is difficult in multi‐cell hosts due to developmental lethality of mutations. Mycobacterium marinum (Mm) is an established model for tuberculosis, a disease afflicting nearly one‐third of the world's population. We found that Mm‐infected Caenorhabditis elegans display >80% mortality, but nonpathogenic M. smegmatis cause <15% mortality. C. elegans displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
(122 reference statements)
1
15
0
Order By: Relevance
“…Although previous studies have shown that TOL-1 is important for early development and pathogen recognition in C. elegans , the downstream pathways activated by TOL-1 during early development remain unclear ( 53 , 57 ). Recently, Brandt and colleagues revealed that TOL-1 contributes to the development and function of BAG neurons required for the pathogen-avoidance behavior in C. elegans via TOL-1-to-p38 MAPK pathway ( 51 , 58 ). In addition, C. elegans with a TOL-1 mutation is more susceptible to certain bacterial infections than the wild type, suggesting that TOL-1 also likely participates in microbial defense ( 53 , 56 , 59 , 60 ).…”
Section: Tlrs In Invertebratesmentioning
confidence: 99%
“…Although previous studies have shown that TOL-1 is important for early development and pathogen recognition in C. elegans , the downstream pathways activated by TOL-1 during early development remain unclear ( 53 , 57 ). Recently, Brandt and colleagues revealed that TOL-1 contributes to the development and function of BAG neurons required for the pathogen-avoidance behavior in C. elegans via TOL-1-to-p38 MAPK pathway ( 51 , 58 ). In addition, C. elegans with a TOL-1 mutation is more susceptible to certain bacterial infections than the wild type, suggesting that TOL-1 also likely participates in microbial defense ( 53 , 56 , 59 , 60 ).…”
Section: Tlrs In Invertebratesmentioning
confidence: 99%
“…For the C. elegans co-infection liquid assay, methodology with few modifications was used (Brenner 1974;Hae-Eun et al 2017). Alternatively, for infection, specific numbers of CFU of M. marinium treated with 2,2-BP bacteria from an overnight culture were directly inoculated into the liquid medium for feeding or to infect the nematodes for 7 days plates were incubated at 25 °C, animals were scored as live or dead on a daily basis and images were taken on the 7th day of infection at 10× magnification equipped with Coslab camera (Galbadage et al 2016).…”
Section: Maintenance and Survival Of Caenorhabditis Elegansmentioning
confidence: 99%
“…To evaluate the consequences of iron deficiency in MTB, the colonization of C. elegans, an established infection model for mycobacteria (Galbadage et al 2016), was tested. Antimycobacterial effects of iron restriction were validated in C. elegans nematode model infected with M. marinum.…”
Section: Iron Restriction Inhibited the Virulence Of M Marinum In C Elegansmentioning
confidence: 99%
“…None of the known canonical DNAsensing pathways identified in higher eukaryotes are conserved in C. elegans. While the C. elegans genome does encode one TLR (TOL-1) (Pujol et al 2001), it appears to have a limited role in immunity (Tenor and Aballay 2008;Galbadage et al 2016;Rangan et al 2016;Battisti et al 2017); furthermore, the immune functions of TOL-1 may operate mainly via a developmental function (Brandt and Ringstad 2015). The absence of these systems suggests that C. elegans may possess alternative and novel pathways to fulfill this important defense function.…”
Section: Discussionmentioning
confidence: 99%